Translating basic mechanisms of IgG effector activity into next generation cancer therapies. - Nimmerjahn, Falk; Ravetch, J. V. (Cancer Immunity, 2012)
Monoclonal antibodies of the immunoglobulin G (IgG) isotype have become a well-established therapeutic tool for the targeting of malignant cells in tumor patients. Despite tremendous success in the treatment of lymphoma and breast cancer, it has also become clear that we may not be able to further improve antibody therapy of cancer by simply generating more tumor-specific antibodies with a higher affinity. Instead, the work of many groups in the past years suggests that optimizing the recruitment of effector functions provided by the adaptive and innate immune systems via engineering of the IgG constant domain may hold great promise to achieve enhanced therapeutic activities. A major goal in cancer therapy would be to initiate adaptive immune responses to the patient's tumor that would result in long-term protection against recurrence. The use of immunostimulatory antibodies shows great promise in stimulating adaptive immune responses. Surprisingly, recent studies also implicate an important role for the antibody constant domain in the activity of these molecules in vivo, opening up new possibilities to further improve the activity of immunomodulatory antibodies by Fc engineering.